Multifunctional ultrawideband antennas : trends, techniques and applications - Saha, Chinmoy; Siddiqui, Jawad Y.; Antar, Yahia (Boca Raton : CRC Press, 2019)
Multifunctional Antennas (MFA) are comparatively a new area for antenna research and finds applications in various modern wireless radios, like Cognitive Radio (CR) in Software Defined Radio (SDR) technology and MIMO technology. This book is first attempt and an invaluable resource which deals with the design and realization of various kinds of multifunctional antennas. After clearly explaining the exclusive features of MFAs, the book presents various designs of such antennas considering versatile modern and upcoming applications. Written by three internationally known researchers, Multi-Functional Ultra Wideband Antennas: Trends, Techniques and Applications: Provides a lucid introduction on UWB systems, historical perspective and discusses various applications of such systems Discusses fundamentals of antennas and its characterization in time and frequency domains, primarily aimed for the beginners in the area Revisits the design and realization of various classical UWB antennas Discusses various techniques of designing frequency-notched UWB antennas and provide detailed comparison of the techniques Deals with the techniques of deriving multiple antenna functionalities from a single antenna Incorporates exclusive discussions on modern reconfigurable antennas and printed and dielectric resonator based MIMO antennas with clear focus on recent and upcoming technological requirements With Multi-Functional Ultra Wideband Antennas: Trends, Techniques and Applications, antenna engineers, communication system engineers, graduate students, academic/industry researchers will gain a thorough knowledge on design of such antennas with clear physical insight and understanding. Chinmoy Saha, PHD, is an associate Professor in the Department of Avionics at Indian Institute of Space Science and Technology, Thiruvananthapuram, Kerala, India. His current research interest includes Microwave Circuits, Engineered Materials, Metamaterial Inspired Antennas and Circuits, reconfigurable and multi-functional antennas for modern wireless applications, Dielectric Resonator antennas, THz antennas and wireless power transfer. He is the author or coauthor of several books, scientific journals and recipient of several prestigious awards. Jawad Yaseen Siddiqui, PHD, is an associate Professor in the Department of Radio Physics and Electronics at University of Calcutta, Kolkata, India. His current research interest includes ultra-wideband antennas, frequency recongurable antennas, tapered slot antennas and multi-functional antennas for cognitive radio application. He is the author or coauthor of several books, scientific journals and recipient of prestigious awards. He is a Co-Principal Investigator on Stratosphere Troposphere (ST) Radar Project at the University of Calcutta, Kolkata, India. Yahia M.M. Antar, PHD, is a Professor in the Department of Department of Electrical and Computer Engineering at the Royal Military College of Canada, Kingston, ON, Canada. He is the author or coauthor of several books, scientific journals and recipient of prestigious awards which includes IEEE-Antennas and Propagation Society prestigious Chen-To-Tai Distinguished Educator Award for 2017, 2015 IEEE Canada J. M. Ham outstanding Engineering Education Award, 2014 IEEE Canada RA Fessenden Silver Medal, 2012 Queen's Diamond Jubilee Medal from the Governor General of Canada and many more.
2.4.5.1 Modes and Radiation Mechanisms of DRAs2.4.5.2 Broadband DRA Techniques; 2.4.6 UWB Antennas for Special Applications; References; 3: Frequency-Notched UWB Antenna Design; 3.1 Introduction; 3.2 Spectrum Overlapping Between UWB and Narrowband Services; 3.2.1 RF Spectrum; 3.2.2 Interference Aspects; 3.3 Techniques of Frequency-Notched UWB Antennas; 3.3.1 Modifications on the Radiator; 3.3.2 Modifications on the Ground Plane or Signal Line; 3.3.3 Integrated Filter Techniques; 3.3.4 Metamaterial-Inspired Resonators; 3.3.4.1 Calculation of SRR's Resonance Frequency; 3.3.4.2 Circular SRR
OCLC-licensed vendor bibliographic record.
Keywords: Ultra-wideband antennas; TECHNOLOGY & ENGINEERING / Mechanical; SCIENCE / Physics; TECHNOLOGY / Microwaves